2019
DOI: 10.21203/rs.2.10413/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Root system traits impact early fire blight susceptibility in apple (Malus × domestica)

Abstract: Background Although it is known that resistant rootstocks facilitate management of fire blight disease, incited by Erwinia amylovora, the role of rootstock root traits in providing systemic defense against E. amylovora is unclear. In this study, the hypothesis that rootstocks of higher root vigor provide higher tolerance to fire blight infection in apples is tested. Several apple scion genotypes grafted onto a single rootstock genotype and non-grafted ‘M.7’ rootstocks of varying root vigor are used to assess … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For instance, selection of appropriate allelic combinations from HIPM/DIPM genes can lower successful pathogen infection, leading to reduced fire blight susceptibility. The root system can also influence fire blight susceptibility levels through co-regulated gene expression patterns and system-level interactions between carbohydrate and defense pathways 63 . Therefore, allelic combinations for the optimal root system can be used to breed rootstocks to further reduce fire blight susceptibility of grafted scions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, selection of appropriate allelic combinations from HIPM/DIPM genes can lower successful pathogen infection, leading to reduced fire blight susceptibility. The root system can also influence fire blight susceptibility levels through co-regulated gene expression patterns and system-level interactions between carbohydrate and defense pathways 63 . Therefore, allelic combinations for the optimal root system can be used to breed rootstocks to further reduce fire blight susceptibility of grafted scions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted the role of belowground plant parts, including roots and endophyte communities, in plant defensive strategies against aboveground pathogens (Erb et al 2009, Busby et al 2016). One such strategy, for example, depends on inter‐organ signaling to reduce the plant's nutrient status via changes to root trait expression, which instigates systemic stress‐responsive pathways to limit aboveground disease (Singh et al 2019). Research has shown that these systemic responses can be induced by specific organic amendments, including different compost types (Kavroulakis et al 2005) and biochar (Elad et al 2010), via biotic and chemical elicitors that trigger specific disease pathways within the host plant (Walters et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…When confronted with pests and pathogens aboveground, belowground resource acquisition strategies often indicate plant defence strategies. While previous studies have revealed a decoupling of above and belowground plant traits (Freschet et al 2013, Isaac et al 2017), variations in individual root functional trait expression and root‐associated endophyte communities can play an important role in 1) regulating systemic plant defense strategies (by way of inter‐organ signaling) (Erb et al 2009); 2) altering the plant's nutrient status via shifts in root trait expression (Singh et al 2019); 3) inciting competition for plant resources via collaboration with specific root endophyte community members (Fritz et al 2006, Li et al 2018); and/or 4) enhancing plant tolerance of aboveground disease with compensatory growth via greater root resource acquiring traits or specific beneficial microbial collaborations (Tchameni et al 2011). However, the persistence of established belowground trait relationships within visibly diseased plant environments remains largely unclear (Freschet et al 2021).…”
Section: Introductionmentioning
confidence: 99%